Managing HeterogeneousWSNs in Smart Cities: Challenges and Requirements - Cao Minh, Trang; Bellata, Boris; Oechsner, Simon; Liao, Ruizhi; Oliver, Miquel (EAI Endorsed Transactions on Internet of Things, 2016)
The dramatic advances in wireless communications and electronics have enabled the development of Wireless Sensor Networks (WSNs). WSNs consist of many aordable and portable sensor nodes for collecting data from the environment. In this tutorial article, we address management requirements of WSNs through presenting some key management scenarios in the Smart Cities context, such as intelligent transportation systems, smart grids and smart buildings. The limited resources and heterogeneous characteristics of WSNs pose new challenges in network management, which include the presence of various faults, the diÿculty in replacing and repairing a large number of sensor nodes, the existence of an uncertain topology, and the resource allocation. To cope with these challenges, we first discuss advantages and disadvantages of centralized and distributed management approaches and then discuss the benefit of a multilevel management schema. Next, we present in detail the specific features for a management system of WSN in Smart Cities context (WSN-iSC) such as lightweight, self-detection, self-configuration, sharing infrastructure, service monitoring, plug and play, context awareness and interoperability. Finally, we discuss several key enabling technologies for management systems, such as policy based and agent based approaches, as well as we introduce some middleware solutions. This tutorial article aims to be a first reference for any reader interested in WSN-iSC management solutions. It provides an insightful and comprehensible introduction to the scenarios, requirements, open challenges, problems, key technologies and desired features that will shape future developments on this field, as well as it surveys the most relevant and recent works from the literature.
Keywords: sensor networks; network management; resources allocation; self configuration; context aware